Influência da interação de complexos tricarbonilrênio(I) com biomoléculas nos efeitos citotóxicos em células tumorais - Lavor, Tayná Saraiva de (2023)
In recent years, Re organometallic compounds have been shown extremely promising as candidates for anticancer drugs. Several compounds exhibited cytotoxicity equal to or greater than well-established anticancer drugs based on platinum or organic molecules. This work aims to evaluate how the interaction degree of tricarbonylrhenium(I) complexes containing polypyridyl groups such as fac-[Re(CO)3(phen)(py)]+, fac-[Re(CO)3(dpq)(py)]+ e fac-[Re(CO)3(dppz)(py)]+ with biomolecules (protein, lipid and DNA), may influence the cytotoxic effect on tumor cells. In addition to establishing the relationship between the degree of hydrophobicity and the interaction of these compounds with biomolecules. First, the partition coefficient (Kp) of the three complexes studied was determined, in order to evaluate the lipophilicity tendency. Results showed that fac-[Re(CO)3(dppz)(py)]+ has higher Kp and Log P values compared to complexes of [Re(CO)3(phen)(py)]+ and [Re(CO)3(dpq)(py)]+. Interaction between the tricarbonylrhenium(I) complexes and BSA (Bovine Serum Albumin) protein was also investigated, using physicochemical parameters such as the Stern-Volmer constant (Ksv) and binding constant (Kb). Data indicated higher Ksv and Kb values for fac-[Re(CO)3(dppz)(py)]+ than for [Re(CO)3(phen)(py)]+ and [Re(CO)3(dpq)(py)]+, suggesting that the greater hydrophobicity of [Re(CO)3(dppz)(py)]+ favors the interaction with protein. The interaction of Re complexes with lipids (DOPG liposome models) and DNA was also evaluated, results showed the same tendency followed by BSA. In other words, the [Re(CO)3(dppz)(py)]+ complex also showed higher Kb value compared to [Re(CO)3(phen)(py)]+ and [Re( CO)3(dpq)(py)]+ in liposomes and DNA. Incorporation experiments were carried out using the UV-Vis technique, but it was not possible to evaluate with such clarity, since the absorbances of the complexes were low. In the cytotoxicity assay, it is noted that [Re(CO)3(dppz)(py)]+ showed the highest cytotoxicity (IC50 ≈ 9 µM) among the studied compounds (IC50 > 20 µM). This greater cytotoxicity of [Re(CO)3(dppz)(py)]+ may be related to the greater interaction of the dppz ligand with DNA and/or also to greater permeation in the lipid bilayers of cells, confirmed by the higher values of Kp and Kb to DNA. Basically, interaction studies of Re complex with biomolecules (proteins, DNA and lipids) revealed that a greater alkyl chain of ligands in the complex, greater interaction with biomolecules, and as a consequence greater cytotoxicity in tumor cells.